2015
DOI: 10.1016/j.diabet.2014.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of growth hormone induced JAK2 and mTOR signalling by hepatic protein tyrosine phosphatase 1B

Abstract: Protein tyrosine phosphatase 1B (PTP1B) regulates various signalling pathways including insulin, leptin, IGF-1 and growth hormone (GH) signalling. Transmission of the GH signal depends on JAK2, which is how PTP1B is thought to modulate GH signalling in the liver, based on studies utilising global PTP1B knockout mice (Ptp1b -/-). Here, we investigated the liver-specific role of PTP1B in GH signalling, using liver-specific Ptp1b -/-mice (alb-crePtp1b -/-), under physiological (chow) or insulin resistant (high-fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The same authors showed that PTP-1B KO mice were characterized by the increased STAT5β phosphorylation and, in consequence, the increased level of the IGF-1 in liver was stated. Also Owen et al [ 108 ] planned a study to investigate the role of PTP-1B in GH signal transduction in the liver. This team conducted an experiment on mice with the local deletion of the gene coding PTP-1B protein (liver-specific PTP-1B −/− ) and compared the impact of standard and high-fat diets.…”
Section: Ghr-jak2-stat Inhibitorsmentioning
confidence: 99%
“…The same authors showed that PTP-1B KO mice were characterized by the increased STAT5β phosphorylation and, in consequence, the increased level of the IGF-1 in liver was stated. Also Owen et al [ 108 ] planned a study to investigate the role of PTP-1B in GH signal transduction in the liver. This team conducted an experiment on mice with the local deletion of the gene coding PTP-1B protein (liver-specific PTP-1B −/− ) and compared the impact of standard and high-fat diets.…”
Section: Ghr-jak2-stat Inhibitorsmentioning
confidence: 99%
“…However, the fact that IGF-I levels remain significantly lower in individuals with NAFLD after corrections for weight, waist circumference, and diabetes ( 25 ) suggests that their livers are resistant to the actions of GH. In fact, mice made obese by high-fat feeding fail to respond to an acute injection of GH by increasing the level of hepatic pStat5b ( 26 ), where the GHR/Jak2/Stat5b signal transduction pathway is required for GH-mediated regulation of IGF-I gene expression ( 27 ). In addition, rats fed a high-fat, low-carbohydrate diet exhibited a decrease in hepatic expression of the GHR (mRNA and protein), pStat5b protein, and IGF-I mRNA levels ( 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…Relevant in wild-type fasted mice, the GH resistance state develops, which is manifested by disorders in somatotropic axis at the GHR level, whereas in fasted PTP-1B KO mice, despite starvation, GH resistance state does not develop. PTP-1B KO mice are characterized by increased STAT5b tyrosine phosphorylation and augmented level of IGF-1 [87,88]. The PTP known as Src homology 2 (SH2) containing protein tyrosine phosphatase (SHP-1) was initially described in the hematopoietic system [89].…”
Section: Protein Phosphatases and Signal Regulatory Proteins (Sirps)mentioning
confidence: 99%